The Lombard– Carolingian role in the emergence of the Croatian Principality: North Italian influences and their modern interpretations - Vedriš, Trpimir (2009)
Departing from the interpretation of particular Dalmatian three-apse/altar churches as the evidence of the Ambrosian liturgy in the Croatian Principality, brought forth by the Croatian art historians around 1990, I analyze the “ north Italian thesis” which gained much favor in Croatian historiography during the last decade of the 20th c. This “ new historiographic perspective” influenced some of the most prominent Croatian medievalists and reached its apogee with the exhibition “ Croats and Carolingians” held in Split and Brescia in 2000/2001 and 2001/2002, respectively. Probably the most elaborate vision of this “ new perspective” is to be found in the work of M. Ančić, who in the series of papers elaborated the thesis stressing the crucial importance of the Lombards-Carolingians in the formation of Croatian Early Medieval Principality. In his view this “ Lombard-Frankish” thesis can be summarized as follows: a) the Croats were among the other Slavic gentile warrior groups moved by the Charlemagne from the Elba-Vistula region into Dalmatia ; b) the Croats found almost no traces of organized forms of social life in Dalmatia ; c) they formed the core of the local aristocracies ; and finally d) in the period 822-888 the region between Drava and Adriatic became controlled by the Croats as the vassals of the Emperor and the part of the Kingdom of Italy, hierarchically dependent of the markgraves of Friuli. Finding first two of these points problematic, here I concentrate on the fourth point, namely the question of the Frankish “ institutions and forms of social conduct” which were allegedly transplanted from the Northern Italy. Narrowing my focus down to the problem of the missionary activities of the Lombard monks in Croatian principality, I propose to examine previously unemployed evidence of the possible relations between North Italy and the Dalmatian hinterland during the 9th c. Seeing the “ boom” of the “ Carolingian perspective” , to a certain extent, as the result of the political changes in the 1990s, I finally maintain that some of the issues raised in that context truly represent relevant and welcome “ new perspective” in the study of Early Medieval Croatia.
Projekt MZOS
ENG